Barriers in accessing care services for physically disabled in a hospital setting in Riyadh, Saudi Arabia, cross-sectional study - Fatimah MohammedAli Alkawai; Abdullah Saad Alowayyed (Greater Baltimore Medical Center, 2017)
Objective: The aim of this study was to identify the significant difficulties in access to health care services experienced by patients with physical disabilities. Method: A cross-sectional study at King Abdul Aziz Medical City, Riyadh, Saudi Arabia on 235 persons with physical disability, from 1 January to 30 June 2014. Results: A total of 88% of the people with disability reported having the need for someone to accompany them. Over 52% were unsatisfied with parking, 49.8% with the waiting area, 51.3% with wheel-chair services, and nearly 45% were unsatisfied with toilet facilities for the physically disabled. Those who were wheel-chair bound had statistically significant lower mean score for satisfaction with services and facilities related to parking area, reception, and appointment, elevator, and physiotherapy.The majority were satisfied with the attitude of the clinical staff. Conclusion: The majority of patients with physical disability require assistance and cannot move around independently in the healthcare facilities. Nearly half of these patients face several challenges in accessing health care services and are unsatisfied with the services received. Patients with physical disability who are wheel-chair bound have a lesser degree of satisfaction than those who are not wheel-chair bound.